2014
DOI: 10.1021/la404079m
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical Characterization of Dendrimer–Porphyrin Associates at Polarized Liquid|Liquid Interfaces

Abstract: Molecular encapsulation of anionic porphyrins in NH2-terminated polyamidoamine (PAMAM) dendrimers and the interfacial behavior of the dendrimer-porphyrin associates were studied at the polarized water|1,2-dichloroethane (DCE) interface. The formation of the ion associates was significantly dependent on the pH condition and on the generation of dendrimers. 5,10,15,20-Tetrakis(4-sulfonatophenyl)porphyrin (ZnTPPS 4-) associated with the positively charged fourth generation (G4) PAMAM dendrimer was highly stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 38 publications
4
34
0
Order By: Relevance
“…3.5 (PAH), 10 (G4 PAMAM dendrimer), and 20 times (G2 PAMAM dendrimer) larger than for the ZnTPPS 4− system. Taking into account the adsorption of the ion associates involving ZnTPPS 4− , which increases the interfacial concentration of the photoreactant, the potential dependences of the photocurrent measured in the dendrimer−ZnTPPS 4− systems were roughly consistent with the interfacial tension lowering shown in Figure 18 The ΔG D···ZnTPPS 4− values indicate explicitly a high stability of the G4 PAMAM dendrimer−ZnTPPS 4− associate. The ZnTPPS 4− molecule can penetrate into the interior of the larger spherical G4 PAMAM dendrimer, whereas ZnTPPS 4− associated with the small flatelliptical G2 PAMAM dendrimer is exposed to the outer solution phase.…”
Section: Effects Of Cationic Additives For Photocurrentsupporting
confidence: 67%
See 1 more Smart Citation
“…3.5 (PAH), 10 (G4 PAMAM dendrimer), and 20 times (G2 PAMAM dendrimer) larger than for the ZnTPPS 4− system. Taking into account the adsorption of the ion associates involving ZnTPPS 4− , which increases the interfacial concentration of the photoreactant, the potential dependences of the photocurrent measured in the dendrimer−ZnTPPS 4− systems were roughly consistent with the interfacial tension lowering shown in Figure 18 The ΔG D···ZnTPPS 4− values indicate explicitly a high stability of the G4 PAMAM dendrimer−ZnTPPS 4− associate. The ZnTPPS 4− molecule can penetrate into the interior of the larger spherical G4 PAMAM dendrimer, whereas ZnTPPS 4− associated with the small flatelliptical G2 PAMAM dendrimer is exposed to the outer solution phase.…”
Section: Effects Of Cationic Additives For Photocurrentsupporting
confidence: 67%
“…The magnitude of the real (i photo,re ) and imaginary (i photo,im ) components of the ac photocurrent measured at pH 5.3 and 7.2 increased gradually at positive potentials. In our previous study, 18 Figure 4). In general, the concentration of a surface-active ion at a polarized liquid| liquid interface is maximized around its transfer potential.…”
Section: Spectroscopic Characterizations Of Pamammentioning
confidence: 70%
“…S4, blue lines). These PMF responses were attributed to the ion transfer and adsorption of the dendrimer-bound fluorescent LC species at the organic side of the interface [1,8]. The slight enhancement of the fluorescence intensity confirmed the interaction between LC and the dendrimer as indicated from fluorescence spectra in aqueous solutions (Fig.…”
Section: S5mentioning
confidence: 59%
“…The ion transfer potentials and ionic partition diagrams of HDIP + and HPRO + were, however, not shifted in the presence of the dendrimers. It has been reported that a multipoint electrostatic interaction of ionic species with the dendrimer significantly enhances the ion association stability whereas a monovalent ion is not appreciably associated with the dendrimer [23,24]. The ambiguous effects of the dendrimer for the monovalent drug cations could be due to weak interaction with the G3.5 PAMAM dendrimer.…”
Section: Voltammetric Responses Of Ionizable Drugs Affected By the Dementioning
confidence: 99%
“…The spectroelectrochemical analysis of charge transfer reactions elucidated the potential-driven encapsulation of anilinonaphthalenesulfonates in the carboxylate-terminated generation 3.5 (G3.5) polyamidoamine (PAMAM) dendrimer at the polarized water|DCE interface [23]. Recently, The ion association behavior of the amino-terminated PAMAM dendrimers with water-soluble porphyrins at the interface was also investigated in terms of dendritic generation, pH condition, effect of metal center and so on [24]. The PAMAM dendrimer-zinc(II) porphyrin associates showed a high photoreactivity in the heterogeneous photoinduced electron transfer system at the water|DCE interface [25].…”
Section: Introductionmentioning
confidence: 99%